2015
DOI: 10.1038/srep11160
|View full text |Cite
|
Sign up to set email alerts
|

The footprint of urban heat island effect in China

Abstract: Urban heat island (UHI) is one major anthropogenic modification to the Earth system that transcends its physical boundary. Using MODIS data from 2003 to 2012, we showed that the UHI effect decayed exponentially toward rural areas for majority of the 32 Chinese cities. We found an obvious urban/rural temperature “cliff”, and estimated that the footprint of UHI effect (FP, including urban area) was 2.3 and 3.9 times of urban size for the day and night, respectively, with large spatiotemporal heterogeneities. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
216
2
5

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 300 publications
(246 citation statements)
references
References 35 publications
23
216
2
5
Order By: Relevance
“…We further compared the urban area extracted using nighttime data with that from Landsat data (maximum likelihood classification method). The results showed that the urban area extracted using the method in this study was larger than that from Landsat data ( Table 2); however, it is appropriate for this study due to these reasons: (a) the footprint of SUHI was larger than the actual urban size according to previous studies [40,48,49]; (b) the urbanization primarily occurred in the suburban areas according to previous studies [26,36]; (c) the study period in this study was 2001-2016, the land cover maps used were during 2001-2013, and the urban area may expand during 2014-2016. Finally, we generated the buffer zone between 20 and 25 km from the urban areas, and we excluded the pixel with DN > 10 (SNLD) in the 20-25 km buffer and defined it as rural area [5,41].…”
Section: Extraction Of Urban Areamentioning
confidence: 52%
See 3 more Smart Citations
“…We further compared the urban area extracted using nighttime data with that from Landsat data (maximum likelihood classification method). The results showed that the urban area extracted using the method in this study was larger than that from Landsat data ( Table 2); however, it is appropriate for this study due to these reasons: (a) the footprint of SUHI was larger than the actual urban size according to previous studies [40,48,49]; (b) the urbanization primarily occurred in the suburban areas according to previous studies [26,36]; (c) the study period in this study was 2001-2016, the land cover maps used were during 2001-2013, and the urban area may expand during 2014-2016. Finally, we generated the buffer zone between 20 and 25 km from the urban areas, and we excluded the pixel with DN > 10 (SNLD) in the 20-25 km buffer and defined it as rural area [5,41].…”
Section: Extraction Of Urban Areamentioning
confidence: 52%
“…Finally, we generated the buffer zone between 20 and 25 km from the urban areas, and we excluded the pixel with DN > 10 (SNLD) in the 20-25 km buffer and defined it as rural area [5,41]. The rural areas in this study were set larger than previous studies, since the footprint of UEs was much larger than the urban areas in previous studies [5,40,48,49]. We did not select larger buffer zones for reducing the uncertainties due to different climate conditions and topography [48].…”
Section: Extraction Of Urban Areamentioning
confidence: 96%
See 2 more Smart Citations
“…By 2025 it is projected that there will be 50 Mega Cities with the fastest growth occurring in Africa and Asia. Urban expansion is usually characterized as increasing impervious surface areas and losing agricultural and forest lands bring many well-recognized environmental consequences such as water shortages [21,22], water and air pollution [23], and urban heat island [24]. In particular, urbanization affects watershed microclimate, surface water dynamics, groundwater recharge, stream geomorphology, biogeochemistry, and stream ecology [23,25].…”
Section: Population Growth Urbanization Land Use Change and Demogrmentioning
confidence: 99%